Roth spots in pyridoxine dependent epilepsy. (18th August 2011) - Bok, Levinus A; Halbertsma, Feico; Kerkhoff, Frank; Jakobs, Cornelis; Duijsters, Carola; Willemsen, Michèl
Abstract : Pyridoxine dependent epilepsy (PDE) is a rare metabolic defect in the degradation of lysine. The authors report a patient with metabolic and DNA confirmed PDE, on the fifth day of life ophthalmoscopy showed bilateral multiple white centred retinal haemorrhages, so called Roth spots. Roth spots are non-specific haemorrhagic signs that occur in a variety of conditions of acute systemic insults in homeostasis – most often infections- which relate to retinal capillary damage and the ensuing reparative process. No biochemical or microbiological signs of infection were present in blood and liquor. MRI of the brain showed an abnormal diffusion signal with increased apparent diffusion coefficient and little blood around the tentorium. The knowledge of the pathogenesis of PDE is still limited. The presence of Roth spots is suggestive for a pathogenic mechanism of vasogenic damage in PDE.